2015
DOI: 10.1037/lhb0000134
|View full text |Cite
|
Sign up to set email alerts
|

Lay understanding of forensic statistics: Evaluation of random match probabilities, likelihood ratios, and verbal equivalents.

Abstract: Forensic scientists have come under increasing pressure to quantify the strength of their evidence, but it is not clear which of several possible formats for presenting quantitative conclusions will be easiest for lay people, such as jurors, to understand. This experiment examined the way that people recruited from Amazon's Mechanical Turk (n ϭ 541) responded to 2 types of forensic evidence-a DNA comparison and a shoeprint comparison-when an expert explained the strength of this evidence 3 different ways: usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 50 publications
7
66
0
Order By: Relevance
“…There appears to have been no advice in the judgement what to do with this figure of 1 billion. The word 'match' invites the prosecutor's fallacy as lay-persons can easily believe that a 'match' is synonymous to 'identification' [80]. There is the implicit risk of confirmation bias where evidence inconvenient to the prosecution is ignored or underweighted [81] and there is the associated danger that apparently compelling 'evidence' may be used to infer the activity (i.e.…”
Section: (7)mentioning
confidence: 99%
“…There appears to have been no advice in the judgement what to do with this figure of 1 billion. The word 'match' invites the prosecutor's fallacy as lay-persons can easily believe that a 'match' is synonymous to 'identification' [80]. There is the implicit risk of confirmation bias where evidence inconvenient to the prosecution is ignored or underweighted [81] and there is the associated danger that apparently compelling 'evidence' may be used to infer the activity (i.e.…”
Section: (7)mentioning
confidence: 99%
“…These inverse fallacies can take the form of equating likelihood ratios with the probability that the defendant is guilty (the prosecutor's fallacy) or of understanding the likelihood ratio to indicate that a sizable number of people could have been the source of the evidence (the defense attorney's fallacy). Second, people find it difficult to properly comprehend probabilistic evidence, especially for extreme values, and seem insufficiently sensitive to those values when adjusting their posterior judgments of guilt (Koehler 2012, Thompson & Newman 2015, Thompson et al 2018.…”
Section: Probabilistic Evidencementioning
confidence: 99%
“…However, in this case, this is even more important because, in a forensic case, end-users are typically not proficient in mathematics and statistics, and care should be taken in order to explain the performance results if requested on trial (in any case, the authors discourage the use of complex performance representations on trial given the difficulties of human beings in general and triers of fact in particular to understand forensic statistics. A recent study about this can be found in [ 40 ]).…”
Section: Experimental Examplesmentioning
confidence: 99%